Suppressed Charge Recombination in Inverted Organic Photovoltaics via Enhanced Charge Extraction by Using a Conductive Fullerene Electron Transport Layer - Li, Chang-Zhi; Chang, Chih-Yu; Zang, Yue; Ju, Huan-Xin; Chueh, Chu-Chen; Liang, Po-Wei; Cho, Namchul; Ginger, David S.; Jen, Alex K.-Y. (Advanced materials (Weinheim), 2014)
Conductive fullerene electron‐transporting layers (ETLs) are developed to facilitate the solution processing of highly efficient inverted OSCs with power conversion efficiency (PCE) reaching 9.6%. Its high conductivity also allows devices to be fabricated independently of the ETL thickness (up to ca. 50 nm). Transient photovoltage (TPV) measurements are used to shed light on how these conductive ETLs help suppress charge recombination in solar cells.